Familial occurrence of imperforate hymen in premature monozygotic twins and their mother: a case report and literature review - Bernadine Han Ern Chua; Zubair Amin; Zubair Amin; Yvonne Peng Mei Ng; Yvonne Peng Mei Ng (Frontiers Media S.A., 2024)
BackgroundImperforate hymen is an uncommon obstructive anomaly of the developing female reproductive tract. There are occasional case reports of imperforate hymen occurring in family clusters, suggesting a plausible familial mode of inheritance. We describe a set of monozygotic premature twins with imperforate hymen noted at birth, whose mother was diagnosed with the same condition as a teenager. We also elucidate the likely underlying mode of inheritance of imperforate hymen.MethodWe utilized the CARE (Case Report) guideline in reporting the cases.Case presentationThese are monozygotic twins born prematurely at 30 weeks of gestation, noted at birth to have bulging cyst-like structures protruding from their vaginas. The twins were not dysmorphic and did not have any other congenital malformations. Over the next few weeks, these cyst-like structures (mucoceles) became less prominent. The genital anomaly was diagnosed as imperforate hymen. Their mother was also diagnosed with an imperforate hymen when she was 12 years old and was treated with hymenectomy.DiscussionThis unique occurrence of imperforate hymen in a set of premature monozygotic twins and their mother suggests a plausible autosomal or X-linked dominant mode of inheritance. Given the role of genetic inheritance in imperforate hymen development, it is important to screen female relatives of an index case for this genital anomaly.